Polyimide varnish and polyimide coating material prepared therefrom
The use of nano-silicon dioxide with controlled zeta potential and organosilane treatment in polyimide varnish addresses the issue of pulse durability, enhancing insulation and corona resistance in electrical devices.
Patent Information
- Application Number
- CN202410858214.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
Existing polyimide coatings lack sufficient pulse durability, leading to premature insulation breakdown and reduced lifespan in electrical devices under high voltage conditions due to corona discharge and ozone/ion generation.
A polyimide varnish comprising nano-silicon dioxide with a controlled zeta potential range and surface-modified with organosilane is used, enhancing dispersibility and improving pulse durability through improved insulation and corona resistance.
The polyimide varnish and its cured products exhibit enhanced pulse durability, withstanding higher voltages and maintaining insulation integrity for extended periods, thus extending the life of electrical devices.
Smart Images

Figure CN119220171A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority under 35 U.S.C. §119 to Korean Patent Application No. 10-2023-0084737 filed in the Korean Intellectual Property Office on June 30, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The following disclosure relates to a polyimide varnish and a polyimide coating material prepared therefrom, and more particularly to a polyimide varnish having excellent pulse durability and a polyimide coating material prepared therefrom. Background Art
[0004] Usually, polyimide resin refers to the highly heat-resistant resin obtained by carrying out solution polymerization on aromatic dianhydride and aromatic diamine or aromatic diisocyanate to produce polyamic acid derivatives, then closed-loop dehydration and imidization at high temperature. Polyimide resin is a kind of insoluble, infusible, ultra-high heat-resistant resin, and has excellent performance such as thermal oxidation resistance, heat resistance, radiation resistance, low temperature characteristics, chemical resistance, etc., and is thus used in a wide range of fields, including heat-resistant advanced materials such as motor vehicle materials, aviation materials and spacecraft materials, and electronic materials such as insulating coatings, insulating films, semiconductors and TFT-LCD electrode protection films. In recent years, polyimide resin is also used for display materials such as optical fiber and liquid crystal orientation film, transparent electrode film by including conductive fillers in the film or carrying out surface coating, etc.
[0005] In particular, in an insulated wire used as a coil winding of a motor, for example, an insulating layer (insulating coating film) coating a conductor requires excellent insulation, adhesion to the conductor, heat resistance, mechanical strength, etc. Therefore, polyimide is used as a resin to form the insulating layer.
[0006] However, in electrical devices with high applied voltage, such as motors using high voltage between insulating layers or coating materials, high voltage is applied to insulated wires constituting the electrical devices, and there is still a need to develop polyimide having excellent pulse durability characteristics to handle such high voltage.
[0007] In particular, in the case of applying a high voltage, local discharge (corona discharge) is likely to occur on the coating surface, and when the occurrence of corona discharge causes a local temperature rise or the generation of ozone or ions, the coating of the insulated wire may deteriorate, resulting in premature insulation breakdown and shortening the life of the electrical device. Therefore, the use of polyimide as a coating material for a conductor, especially as a coating material for a case of applying a high voltage, requires improvement in pulse durability characteristics such as insulation breakdown voltage performance or corona discharge initiation voltage. Summary of the invention
[0008] Embodiments of the present disclosure are directed to providing a polyimide varnish having excellent pulse durability.
[0009] Another embodiment of the present disclosure is directed to providing a polyimide prepared by imidizing a polyimide varnish.
[0010] Yet another embodiment of the present disclosure is directed to providing a polyimide coating material including a cured product of a polyimide varnish.
[0011] Various modifications can be made in the present disclosure and various embodiments can be implemented, and specific exemplary embodiments are illustrated in the drawings and described in detail. However, these exemplary embodiments are not intended to limit the present disclosure and should be understood to include all modifications, equivalents and substitutes included in the spirit and scope of the present disclosure.
[0012] The terms used in this application are only used to describe specific embodiments and are not intended to limit the present disclosure. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as "including" or "having" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should not be understood as excluding the possibility of the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0013] When amounts, concentrations, or other values or parameters are given herein as ranges, preferred ranges, or lists of desired upper values and desired lower values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether that range is disclosed individually.
[0014] Where numerical ranges are stated herein, it is intended that the endpoints of the range be within that range and that the scope of the invention not be limited to the specific values stated when defining the range unless otherwise indicated.
[0015] As used herein, "dianhydride" is intended to include its precursors or derivatives, which are also referred to as "dianhydrides" or "acid dianhydrides." These products may not technically be dianhydrides, but will still react with diamines to form polyamic acids, and polyamic acids can be converted back to polyimides.
[0016] As used herein, "diamine" is intended to include precursors or derivatives thereof, which may not technically be diamines but will still react with the dianhydride acid to form a polyamic acid, and the polyamic acid can be converted back to a polyimide.
[0017] In addition, unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meanings as those generally understood by those of ordinary skill in the art to which the present disclosure belongs. Terms such as those defined in common dictionaries should be interpreted as having meanings consistent with those in the context of the relevant art, and unless clearly defined in the present application, should not be interpreted in an idealized or overly formal sense. The specific details of the implementation of the present disclosure will be described below.
[0018] Polyimide varnish
[0019] The present disclosure relates to polyimide varnishes having improved pulse durability and useful for applications in conductor coatings.
[0020] In one general aspect, a polyimide varnish is provided, comprising: a polyamic acid comprising a diamine monomer and a dianhydride monomer as polymerization units; and nano-silicon dioxide, wherein the nano-silicon dioxide has an absolute value of a zeta potential of 10.0 mV to 40.0 mV.
[0021] Nano Silica
[0022] The polyimide varnish of the present disclosure may include inorganic particles to improve performance such as pulse durability, wherein the inorganic particles are nano-silica, ie, nano-scale silica (SiO2) particles having an average particle size of 1000 nm or less, and their form and shape are not particularly limited.
[0023] The absolute value of the zeta potential may have a lower limit of 10.5 mV or more, 11.0 mV or more, 11.5 mV or more, 12.0 mV or more, 12.5 mV or more, 13.0 mV or more, 13.5 mV or more, 14.0 mV or more, 14.5 mV or more, or 15.0 mV or more, and may have an upper limit of 38.0 mV or less, 35.0 mV or less, 32.0 mV or less, 30.0 mV or less, 28.0 mV or less, 27.0 mV or less, 26.0 mV or less, 25.0 mV or less, 24.0 mV or less, 23.5 mV or less, 23.0 mV or less, 22.5 mV or less, 22.0 mV or less, 21.0 mV or less, 20.5 mV or less, or 20.0 mV or less. By controlling the absolute value range of the zeta potential, high dispersibility can be maintained between the nano-silica in the polyimide varnish without flocculation, thereby improving pulse durability (corona resistance). Here, the zeta potential can be the zeta potential of the nano-silica (silica sol) dispersed in the organic solvent, and the pH of the silica sol can be 2 to 12.
[0024] In an embodiment, the zeta potential of nano-silica dispersed in an organic solvent can be measured by inputting the refractive index, viscosity and dielectric constant of the organic solvent (dispersion medium) into Benano180zeta Pro of Bettersize instruments Ltd. The organic solvent can be any one selected from the group consisting of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), dimethylacetamide (DMAc), dimethylformamide (DMF) and diethylformamide (DEF).
[0025] The organic solvent may have, for example, a refractive index of 1.2 to 1.6 at 25° C., a viscosity of 0.5 cP to 2.0 cP, and a dielectric constant of 30 to 40. Preferably, the organic solvent may have, for example, a refractive index of 1.3 to 1.5 at 25° C., a viscosity of 0.7 cP to 1.7 cP, and a dielectric constant of 32 to 39, more preferably, a refractive index of 1.35 to 1.47 at 25° C., a viscosity of 0.8 cP to 1.0 cP, and a dielectric constant of 35 to 38.5, and more preferably, a refractive index of 1.4 to 1.45 at 25° C., a viscosity of 0.85 cP to 0.95 cP, and a dielectric constant of 37 to 38.
[0026] In an example, nano-silica dispersed in dimethylacetamide can be used (here the solid content concentration of silica is 30 wt %).
[0027] The zeta potential is the potential difference of colloidal particles suspended in a liquid phase. Particles dispersed in a solution have negative (-) or positive (+) charges on their surfaces, and the concentration of (+) ions increases around the (-) charged colloidal particles, forming a Stern layer. Outside the Stern layer is a diffusion layer, which reduces the concentration of (+) ions, thereby achieving a balance between (-) and (+) ions. The potential difference between the starting point of the diffusion layer and the point where the (-) and (+) ions are balanced is called the zeta potential. This zeta potential is used as a measure of the stability of a dispersed sol because it reflects the strength of the repulsive force between the charged particles in the dispersion. The higher the value of the zeta potential, whether negative (-) or positive (+), the stronger the electrical repulsion between the particles, and therefore the distance between the particles increases to achieve a stable state without agglomeration. The value of the zeta potential can be used to determine a measure of dispersion stability. In other words, the greater the absolute value of the zeta potential, the better the dispersibility. Furthermore, different solvents, concentrations, pH, functional groups and surface properties of the particles can result in different zeta potential values and therefore need to be compared as a measure of stability.
[0028] In addition, the average particle size of nano-silicon dioxide can be 1 to 200 nm, particularly, for example, 5 to 150 nm, 5 to 100 nm, 5 to 70 nm, 10 to 50 nm or 10 to 30 nm. The average particle size can be measured by equipment such as BET, SEM, zeta potential analyzer, etc.
[0029] In addition, the nano-silica may be nano-silica surface-modified with organic silane.
[0030] In addition, the organosilane of the nano-silica surface modified with the organosilane may include at least one selected from the group consisting of methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyldimethylethoxysilane, styrylethyltrimethoxysilane, phenyltrimethoxysilane, Ethoxysilane, p-tolyltriethoxysilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-tert-butoxysilane, vinyltri(isobutoxy)silane, vinyltriisopropenoxysilane, vinyltri(2-methoxyethoxy)silane, N,N-diisopropylethylaminophenyltrimethoxysilane, glycidoxypropyltrimethoxysilane (GPTMS), 3-aminopropyltrimethoxy-silane (APTMS), phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES).
[0031] In addition, the nano-silica with organosilane surface modification can be obtained by combining the compound comprising at least one phenyl group at the terminal and the compound comprising at least one amine group, hydroxyl group, thiol group or epoxide group at the terminal on the surface of nano-silica. Especially, the compound comprising at least one phenyl group at the terminal can be phenyltrimethoxysilane (PTMS) or N-phenyl-3-aminopropyltrimethoxysilane (PAPTES). In addition, the compound comprising at least one amine group, hydroxyl group, thiol group or epoxide group at the terminal can be glycidyloxypropyltrimethoxysilane (GPTMS) or 3-aminopropyltrimethoxy-silane (APTMS).
[0032] Nano-silica surface-modified with organosilane can be prepared by surface-treating nano-silica with organosilane. For example, nano-silica can be obtained by heating organosilane under acidic or alkaline conditions and surface-treating for about 1 to 24 hours. In addition, surface modification can be achieved by other known methods, for example, by mixing organosilane in a solvent, and then reacting at a temperature of 10 to 100° C. or 20 to 60° C. for 1 to 10 hours or 1 to 5 hours to obtain surface-modified nano-silica. In order to combine two or more compounds on the surface of nano-silica, each of the above methods can be performed.
[0033] The nano-silica surface-modified with organosilane disclosed in the present invention can prevent the agglomeration of inorganic particles in the polyimide varnish, and can enhance the interaction with the solid content (polyamic acid) due to the functional group of the compound, thereby improving the dispersibility and miscibility.
[0034] Based on 100 weight portions of the polyimide solids content contained in the total polyimide varnish, nano silicon dioxide can also account for the amount of 4 to 30 weight portions.For example, the lower limit of the amount of nano silicon dioxide can be 4.3 weight portions or more, 4.5 weight portions or more, 4.8 weight portions or more, 5.0 weight portions or more, 5.3 weight portions or more, 5.5 weight portions or more, 5.7 weight portions or more, 5.8 weight portions or more or 5.9 weight portions or more.In addition, the upper limit of the amount of nano silicon dioxide can be 25 weight portions or less, 20 weight portions or less, 19 weight portions or less, 18 weight portions or less, 17 weight portions or less, 16 weight portions or less, 15 weight portions or less, 14.5 weight portions or less, 14 weight portions or less, 13.5 weight portions or less, 13.3 weight portions or less or 13 weight portions or less. If the amount of nano silica is less than 4 parts by weight, it is ineffective in improving pulse durability, and if the amount thereof is greater than 30 parts by weight, it is undesirable because physical properties may be degraded.
[0035] Polyamic acid
[0036] In the present disclosure, the dianhydride monomer may include at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, Phenylenebis(trimellitic acid monoester anhydride), p-biphenylenebis(trimellitic acid monoester anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,4,5,8-naphthalenetetracarboxylic acid dianhydride and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid dianhydride.
[0037] Preferably, the dianhydride monomer may include at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), and benzophenonetetracarboxylic dianhydride (BTDA), and more preferably pyromellitic dianhydride (PMDA).
[0038] In addition, the diamine monomer may include at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)-4,4'-diamino biphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminodiphenyl ketone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3 -aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenylphenoxy)benzophenone, 3,3'-diamino-4,4'-bis(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenyl sulfide)benzene, 1,3-bis(4-aminophenyl sulfide)benzene, 1,4-bis(4-aminophenyl sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3-Bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-amino)phenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)- bis[4-(4-aminophenoxy)phenyl] ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]thioether, bis[4-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane )phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.
[0039] Particularly, the diamine monomer may include at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP) and 1,3-bis(4-aminophenoxy)benzene (TPE-R), and preferably may include 4,4'-diaminodiphenyl ether (ODA).
[0040] The polyamic acid may include pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA) as polymerization units.
[0041] In the present disclosure, in the total dianhydride monomers, pyromellitic dianhydride (PMDA) may account for a ratio of 50 mol% or more, specifically 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.
[0042] In addition, in the total diamine monomers, 4,4'-diaminodiphenyl ether (ODA) may account for a ratio of 50 mol% or more, specifically 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.
[0043] The polyamic acid solution of the present disclosure can include 95 to 105mol% of dianhydride monomers based on 100mol%. For example, the lower limit of the dianhydride monomer can be 96mol% or more, 97mol% or more, 98mol% or more, 99mol% or more or 99.5mol% or more, and its upper limit can be 104mol% or less, 103mol% or less, 102mol% or less, 101mol% or less or 100.5mol% or less.
[0044] In addition, the molar ratio of the dianhydride monomer to the diamine monomer may be 6:4 to 4:6, preferably 5.5:4.5 to 4.5:6.5, and more preferably 5:5.
[0045] In addition, the polyimide varnish can have a polyimide solid content of 10 to 50wt%. The lower limit of the polyimide solid content can be, for example, 13wt% or more, 15wt% or more, 18wt% or more, 20wt% or more or 25wt% or more, and its upper limit can be, for example, 48wt% or less, 45wt% or less, 43w% or less, 40wt% or less, 38wt% or less, 35wt% or less, 33wt% or less or 30wt% or less. By adjusting the polyimide solid content of the polyimide varnish, the increase of viscosity during the curing process can be controlled and the processing time can be shortened.
[0046] Organic solvents
[0047] In the present disclosure, the polyimide varnish further includes an organic solvent, wherein the organic solvent is not particularly limited as long as it is an organic solvent in which the polyamic acid is soluble, but may be, for example, an aprotic polar solvent.
[0048] In particular, the organic solvent may include at least one selected from the group consisting of: N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropionamide (DMPA), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), 3-methoxy-N,N-dimethylpropionamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diethylene glycol dimethyl ether and naphthalene. Preferably, N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) and the like can be used.
[0049] The organic solvent may further include a modifier comprising a hydroxyl group (OH) or an amine group (NH). Examples of modifiers comprising a hydroxyl group (OH) or an amine group (NH) may include ethylamine, triethanolamine, dimethylamine, trimethylamine, diethylenetriamine, ethylenediamine, tributylamine, pyridine, pyrrolidine, methanol, ethanol, propanol, isopropanol, sec-butyl alcohol, tert-butyl alcohol, n-pentanol, isopentanol, hexanol, octanol, capryl alcohol, nonanol, decanol, undecanol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, allyl alcohol, crotyl alcohol, propargyl alcohol, ethylene glycol, propylene glycol, benzyl alcohol, phenol, etc. The modifier may be controlled to be reactive by reacting with the dianhydride monomer.
[0050] Polyimide varnish and its cured products
[0051] The polyimide varnish may have a temperature of 30°C and 1s -1 The viscosity of the polyimide varnish can be 500 cP to 20,000 cP measured at a shear rate of 1 / s. For example, the upper limit of the viscosity can be 20,000 cP, 15,000 cP, 10,000 cP or lower. The lower limit of the viscosity is not particularly limited, but can be 1,000 cP, 1,200 cP, 1,500 cP or 1,800 cP or higher. The viscosity can be measured using, for example, Haake's Rheostress 600, and can be measured under the conditions of a shear rate of 1 / s, a temperature of 30°C, and a plate gap of 1 mm. The present disclosure can provide a polyimide varnish with excellent processability by adjusting the viscosity range.
[0052] The polyimide varnish may have a haze of 1.5% or less. For example, the upper limit of the haze may be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, or 0.8% or less, and the lower limit is not particularly limited, but may be more than 0%, 0.05% or more, or 0.1% or more. In an embodiment, the haze may be measured using HunterLab equipment according to ASTM E308 standards.
[0053] In addition, the polyimide obtained by curing the polyimide varnish can have a haze of 1.5% or less. For example, the upper limit of the haze can be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less or 0.5%, and its lower limit is not particularly limited, but can be more than 0%, 0.05% or more or 0.1% or more. In an embodiment, the haze can be measured according to the ASTM E308 standard using the equipment of HunterLab, and the polyimide can have a thickness of 20 ± 1.0 μm.
[0054] Furthermore, by using nano-silica having an absolute value range of zeta potential within a predetermined range, the polyimide varnish and a cured product thereof of the present disclosure can prevent agglomeration of nano-silica in the polyimide varnish and can have excellent dispersibility, thereby achieving a low level of haze.
[0055] In addition, the polyimide obtained by curing the polyimide varnish may have an elongation of 25% or more, and the lower limit of the elongation may be, for example, 30%, 33%, 35%, 36%, 37%, 38% or 39% or more. The upper limit is not particularly limited, but may be 80% or less. In an embodiment, the elongation may be determined by curing the polyimide varnish into a polyimide film, cutting the film into 10 mm wide and 40 mm long sheets, and measuring the elongation using an Instron 5564UTM device from INSTRON according to ASTM D-882.
[0056] In addition, the polyimide obtained by curing the polyimide varnish can have a tensile strength of 100MPa or more, and the lower limit of the tensile strength can be, for example, 105MPa, 110MPa, 115MPa, 120MPa, 124MPa or 128MPa or more. Its upper limit is not particularly limited, but can be 400MPa or less. The tensile strength can be determined by preparing a sample having a length of 500mm and a width of 10mm, using an Instron 5564UTM device of INSTRON to measure the tensile strength at a rate of (50mm / min), and calculating the average value of 10 samples.
[0057] In another aspect of the present disclosure, there is provided a polyimide cured product obtained by curing the polyimide varnish as described above, wherein the polyimide cured product may be a polyimide film.
[0058] The polyimide cured product may have a pulse durability of 300 minutes or more, which is the time for the insulating material to withstand a certain voltage according to IEC-60851-5. The lower limit of the pulse durability may be, for example, 330 minutes or more, 370 minutes or more, 400 minutes or more, 450 minutes or more, 500 minutes or more, 550 minutes or more, 600 minutes or more, 650 minutes or more, 700 minutes or more, 720 minutes or more, 750 minutes or more, 770 minutes or more, 800 minutes or more, 820 minutes or more or 830 minutes or more. The upper limit is not particularly limited, but may be 3,000 minutes or less. The pulse durability may be determined by connecting the polyimide coating material to a fixture, applying an AC 1.5-kV voltage (at a frequency of 60 Hz), and measuring the time until a leakage current of 5 mA or more is detected. Here, the thickness of the polyimide may be 26 ± 1.0 μm.
[0059] Furthermore, the polyimide varnish and the cured product thereof according to the present disclosure may have improved pulse durability by using nano-silica having a zeta potential absolute value range within a predetermined range.
[0060] As measured according to ASTM D149 standard, the polyimide cured product can have a breakdown voltage (BDV) of 200 kV / mm or more. The lower limit of the breakdown voltage can be, for example, 205 kV / mm or more, 210 kV / mm or more, 215 kV / mm or more, 220 kV / mm or more, 225 kV / mm or more, 230 kV / mm or more, 233 kV / mm or more, 235 kV / mm or more, 238 kV / mm or more, 240 kV / mm or more, 241 kV / mm or more, or 242 kV / mm or more. The upper limit is not particularly limited, but can be 500 kV / mm or less.
[0061] In still another aspect of the present disclosure, provided is a polyimide prepared by imidizing the polyimide varnish as described above, wherein the polyimide may be in the form of a film.
[0062] In still another aspect of the present disclosure, a polyimide coating material including a polyimide cured product is provided.
[0063] In an embodiment, a method of preparing a polyimide coating material may include coating a polyimide varnish on a surface of a conductor; and imidizing the polyimide varnish coated on the surface of the conductor.
[0064] The conductor may be a copper wire made of copper or a copper alloy, but may also include conductors made of other metal materials, such as silver wire, etc., or various metal-plated wires, such as aluminum-plated or tin-plated wires, etc. The conductor and the coating material may have a thickness according to the KS C3107 standard. The diameter of the conductor may be in the range of 0.3 to 3.2 mm, and the standard film thickness of the coating film (the average value of the maximum film thickness and the minimum film thickness) may be 21 to 194 μm for type 0, 14 to 169 μm for type 1, and 10 to 31 μm for type 2. Depending on the cross-sectional shape of the conductor, the conductor may be a round wire, a rectangular wire, a hexagonal wire, etc., but is not limited thereto.
[0065] In another aspect of the present disclosure, a wire including a polyimide coating material is provided.
[0066] In particular, the wire may be a coated wire including a polyimide coating material, prepared by coating a polyimide varnish on the surface of the wire and then imidizing it. In an embodiment, the coated wire may include a wire; and a coating material in which the polyimide is coated on the surface of the wire and imidized.
[0067] In addition, the present disclosure may provide an electronic device including the coated wire. The electronic device may be, for example, a motor.
[0068] In still another aspect, a component including a molded body formed of a polyimide varnish is provided.
[0069] In particular, the component can be an electronic circuit board component, a semiconductor device, a lithium-ion battery component, a solar cell component, a fuel cell component, a motor winding, an engine peripheral component, a coating, an optical component, a thermal insulation material, an electromagnetic shielding material, a surge component, a dental material, a sliding coating or an electrostatic chuck. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 SEM images of film-type polyimide cured products according to Example 2-1 and Comparative Example 2-1 are shown. DETAILED DESCRIPTION
[0071] The following examples are presented to help understand the present disclosure. The following examples are provided only to make it easier to understand the present disclosure, but the content of the present disclosure is not limited to these examples.
[0072] <Example>
[0073] Preparation Example 1: Nano-silicon dioxide 1 treated with organosilane surface
[0074] Nano-silica 1 (dimethylacetamide-dispersed silica sol, silica solid content concentration of 30wt%, silica average particle size of 10-30nm, average zeta potential (absolute value) of 17.86mV) treated with organosilane surface was prepared. Here, the zeta potential was determined by inputting the refractive index, viscosity and dielectric constant of dimethylacetamide into the Benano180 zetapro device of Bettersize, performing repeated measurements, and then calculating the arithmetic mean.
[0075] Preparation Comparative Example 1. Nano-silicon dioxide
[0076] Nano-silica (silica sol dispersed in N-methylpyrrolidone, with a silica solid content concentration of 30 wt%, an average silica particle size of 10-20 nm, and an average zeta potential (absolute value) of 8.42 mV) was prepared. Here, the zeta potential was determined by inputting the refractive index, viscosity, and dielectric constant of N-methylpyrrolidone into a Benano180 zetapro device of Bettersize, performing repeated measurements, and then calculating the arithmetic mean.
[0077] Preparation of Comparative Example 2. Nano-silica 2 treated with organosilane
[0078] Nano-silica 2 (dimethylacetamide-dispersed silica sol, silica solid content concentration of 30wt%, silica average particle size of 10-20nm, average zeta potential (absolute value) of 4.59mV) treated with organosilane surface was prepared. Here, the zeta potential was determined by inputting the refractive index, viscosity and dielectric constant of dimethylacetamide into the Benano180 zeta pro device of Bettersize, performing repeated measurements, and then calculating the arithmetic mean.
[0079] Preparation of Comparative Example 3. Nano-silica 3 treated with organosilane surface
[0080] Nano-silica 3 (dimethylacetamide-dispersed silica sol, silica solid content concentration of 30wt%, silica average particle size of 10-20nm, average zeta potential (absolute value) of 1.51mV) treated with organosilane surface was prepared. Here, the zeta potential was determined by inputting the refractive index, viscosity and dielectric constant of dimethylacetamide into the Benano180 zeta pro device of Bettersize, performing repeated measurements, and then calculating the arithmetic mean.
[0081] Example 1. Polyimide varnish
[0082] Example 1-1
[0083] In a reaction vessel filled with nitrogen, an organic solvent containing dimethylacetamide (DMAc) and a modifier (0-2 mol%) was added, and the nano-silica surface-treated with an organosilane according to Preparation Example 1 (6 wt% relative to the polyimide solid content) was mixed with pyromellitic anhydride (PMDA) (92 mol%) as a dianhydride monomer and stirred at 40° C. for 30 minutes. Then, 4,4'-diaminodiphenyl ether (ODA) (100 mol%) and pyromellitic anhydride (PMDA) (8 mol%) were added as diamine monomers, stirred, and polymerized at 40° C. for about 1 hour to prepare a polyimide varnish (25 wt% polyimide solid content).
[0084] Example 1-2
[0085] Polyimide varnish is prepared in the same manner as in Example 1, except that nano-silica surface-treated with organosilane (12 wt % relative to the polyimide solid content) is used instead of nano-silica surface-treated with organosilane (6 wt % relative to the polyimide solid content) in Example 1.
[0086] Comparative Examples 1-1 to 1-3
[0087] The polyimide varnish was prepared in the same manner as in Example 1-1, except that the components and amount ratios of the dianhydride monomer, the diamine monomer, and the nano-silica surface-treated with organic silane were adjusted as shown in Table 1 below.
[0088] [Table 1]
[0089]
[0090]
[0091] Example 2. Polyimide cured product (polyimide film)
[0092] Example 2-1
[0093] The polyimide varnish prepared according to Example 1-1 was spun at a high speed of 2,000 rpm to remove air bubbles. Then, the degassed polyimide varnish was applied on a glass substrate (230 mm×230 mm, thickness: 0.55 mm) using a spin coater.
[0094] Next, a film-type polyimide cured product (thickness of 20±1.0 μm or 26±1.0 μm) was obtained by curing under a nitrogen atmosphere at 110° C. (20 minutes) → 150° C. (20 minutes) → 200° C. (20 minutes) → 300° C. (0 minute).
[0095] Example 2-2
[0096] A polyimide cured product was prepared in the same manner as in Example 2-1, except that the polyimide varnish according to Example 1-2 was used instead of the polyimide varnish according to Example 1-1.
[0097] Comparative Example 2-1
[0098] A polyimide cured product was prepared in the same manner as in Example 2-1, except that the polyimide varnish according to Comparative Example 1-1 was used instead of the polyimide varnish according to Example 1-1.
[0099] Comparative Example 2-2
[0100] A polyimide cured product was prepared in the same manner as in Example 2-1, except that the polyimide varnish according to Comparative Example 1-2 was used instead of the polyimide varnish according to Example 1-1.
[0101] Comparative Example 2-3
[0102] A polyimide cured product was prepared in the same manner as in Example 2-1, except that the polyimide varnish according to Comparative Example 1-3 was used instead of the polyimide varnish according to Example 1-1.
[0103] Example 3. Polyimide coating material
[0104] Example 3-1
[0105] In a coating curing furnace, an electric wire including a polyimide coating material having a coating thickness of 110±10 μm was prepared by repeating the process of coating, drying and curing the polyimide varnish according to Example 1-1 on an angular shaped copper wire 20 to 28 times.
[0106] Example 3-2
[0107] A polyimide coating material was prepared in the same manner as in Example 3-1, except that the polyimide varnish according to Example 1-2 was used instead of the polyimide varnish according to Example 1-1.
[0108] <Experimental Example>
[0109] Experimental Example 1. SEM analysis
[0110] The film-type polyimide cured products according to Example 2-1 and Comparative Example 2-1 were analyzed using a scanning electron microscope (particularly VEGA3 model of TESCA), and the SEM images were taken at Figure 1 Shown in.
[0111] like Figure 1 As shown, Comparative Example 2-1 shows particles of 200 nm, which are agglomerated particles of nano-silicon dioxide. At the same time, it can be seen in Example 2-1 that nano-silicon dioxide is uniformly dispersed without agglomeration. Therefore, it is found that the degree of dispersion and agglomeration of nano-silicon dioxide varies depending on the absolute value of the zeta potential.
[0112] Experimental Example 2. Physical Property Evaluation
[0113] Physical properties of the cured products of Examples 2-1 to 2-2 and Comparative Examples 2-1 and 2-2 obtained by curing the polyimide varnishes prepared according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-2 were confirmed in the following manner, and the results are shown in Tables 2 and 3 below.
[0114] (1) Pulse durability
[0115] Pulse durability was determined according to IEC-60851-5 by connecting the polyimide films (thickness 26±1.0 μm) of Examples 2-1, 2-2, and Comparative Example 2-1 to a jig, applying an AC 1.5-kV voltage (frequency 60 Hz), and measuring the time until a leakage current of 5 mA or more was detected. The results are shown in Table 2 below.
[0116] (2) Haze
[0117] The haze of the polyimide varnish (Examples 1-1, 1-2, and Comparative Examples 1-1 to 1-3) was measured using an apparatus of HunterLab according to the ASTM E308 standard, and the results thereof are shown in Table 3 below.
[0118] [Table 2]
[0119]
[0120] [Table 3]
[0121] Polyimide varnish Haze(%) Example 1-1 0.6 Example 1-2 0.6 Comparative Example 1-1 6.2 Comparative Example 1-2 2.7 Comparative Examples 1-3 2.4
[0122] As can be seen from Table 2, the polyimide varnish and film-type cured product thereof of the present disclosure show a significant improvement in pulse durability of about 3 times or more by using nano-silica having a zeta potential within a predetermined range, compared to Comparative Example 2-1.
[0123] In addition, according to Table 3, both the polyimide varnish of the present disclosure and its film type cured product can achieve low-level haze characteristics. In particular, the varnishes of Examples 1-1 and 1-2 show a haze of 0.6%, which is about one-tenth to one-fourth of the haze of Comparative Examples 1-1 to 1-3, indicating that the nano silicon dioxide is not agglomerated and is uniformly dispersed. Comparative Examples 1-1 to 1-3 show that the haze increases due to the agglomeration of materials in the varnish, which can lead to a decrease in mechanical properties and quality.
[0124] The polyimide varnish of the present disclosure may have excellent pulse durability and also provide excellent physical properties such as haze for polyimide.
[0125] The present disclosure may also have excellent applicability as a conductor coating for use in electric vehicle (EV) windings.
[0126] In this specification, detailed descriptions of contents that can be fully recognized and inferred by those skilled in the art of the present disclosure are omitted, and in addition to the specific exemplary embodiments described in this specification, many changes and modifications can be made within the scope of not changing the technical spirit or basic configuration of the present disclosure. Therefore, the present disclosure can also be implemented in a manner different from the manner specifically described and illustrated herein that can be understood by those skilled in the art.
Claims
1. Polyimide varnish, comprising: A polyamic acid comprising a dianhydride monomer and a diamine monomer as polymerized units; as well as Nano-silicon dioxide, The absolute value of the zeta potential of the nano-silicon dioxide is 10.0 mV to 40.0 mV.
2. The polyimide varnish according to claim 1, wherein The nano-silicon dioxide has an average particle size of 1 to 200 nm.
3. The polyimide varnish according to claim 1, wherein The nano silicon dioxide is nano silicon dioxide surface-modified with organic silane.
4. The polyimide varnish according to claim 3, wherein The organosilane of the nano-silica surface modified with the organosilane comprises at least one selected from the group consisting of methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyldimethylethoxysilane, styrylethyltrimethoxysilane, phenyltriethoxysilane, trimethoxysilane, p-tolyltriethoxysilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-tert-butoxysilane, vinyltri(isobutoxy)silane, vinyltriisopropenoxysilane, vinyltri(2-methoxyethoxy)silane, N,N-diisopropylethylaminophenyltrimethoxysilane, glycidoxypropyltrimethoxysilane (GPTMS), 3-aminopropyltrimethoxy-silane (APTMS), phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES).
5. The polyimide varnish according to claim 1, wherein The dianhydride monomer includes at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, paraphenylene Bis(trimellitic acid monoester anhydride), p-biphenylene bis(trimellitic acid monoester anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,4,5,8-naphthalenetetracarboxylic acid dianhydride and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid dianhydride.
6. The polyimide varnish according to claim 1, wherein The diamine monomer includes at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl Benzene, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone , 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3 -aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenylphenoxy)benzophenone, 3,3'-diamino-4,4'-bis(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenyl sulfide)benzene, 1,3-bis(4-aminophenyl sulfide)benzene, 1,4-bis(4-aminophenyl sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3-Bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-amino)phenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)- bis[4-(4-aminophenoxy)phenyl] ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]thioether, bis[4-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane )phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.
7. The polyimide varnish according to claim 1, wherein The polyamic acid includes pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA) as the polymerization units.
8. The polyimide varnish according to claim 1, wherein The polyimide varnish further includes an organic solvent.
9. The polyimide varnish according to claim 8, wherein The organic solvent includes at least one selected from the group consisting of: N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropionamide (DMPA), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), 3-methoxy-N,N-dimethylpropionamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diethylene glycol dimethyl ether and naphthalene.
10. The polyimide varnish according to claim 1, wherein The polyimide varnish has a polyimide solid content of 10 to 50 wt %.
11. The polyimide varnish according to claim 10, wherein The nano silicon dioxide accounts for 4 to 30 parts by weight based on 100 parts by weight of the solid content of the polyimide contained in the total polyimide varnish.
12. The polyimide varnish according to claim 1, wherein The polyimide varnish has a temperature of 30°C and a -1 Viscosities from 500 cP to 20,000 cP measured at shear rates of 1.5 to 2.
0.
13. The polyimide varnish according to claim 1, wherein The polyimide varnish has a haze of 1.5% or less.
14. The polyimide varnish according to claim 1, wherein The polyimide obtained by curing the polyimide varnish has a haze of 1.5% or less.
15. The polyimide varnish according to claim 1, wherein The polyimide obtained by curing the polyimide varnish has an elongation of 25% or more.
16. The polyimide varnish according to claim 1, wherein The polyimide obtained by curing the polyimide varnish has a tensile strength of 100 MPa or more.
17. A polyimide cured product obtained by curing the polyimide varnish according to claim 1.
18. The cured polyimide product according to claim 17, wherein: The polyimide cured product has a pulse durability of 300 minutes or more, the pulse durability being the time an insulating material withstands a certain voltage according to IEC-60851-5.
19. The cured polyimide product according to claim 17, wherein: The polyimide cured product has a breakdown voltage (BDV) of 200 kV / mm or more measured according to ASTM D149 standard.
20. The cured polyimide product according to claim 17, wherein: The polyimide cured product has a breakdown voltage (BDV) of 200 kV / mm or more measured according to ASTM D149 standard.
Citation Information
Patent Citations
Chimeric endolysin ClyY with lytic activity and binding affinity against Clostridium perfringens
KR1020230084737A
Polyimide varnish and preparation method and application thereof
CN109135554A
Novel Saccharomyces cerevisiae strain and use thereof
KR1020230091073A